A List of Best Practices That May Improve the Use of Telephone Interviews During the Recruitment Process - Herron, David; Haglund, Lotta (Evidence Based Library and Information Practice, 2009)
A Review of: Engel, Debra, and Sarah Robbins. "Telephone Interviewing Practices within Academic Libraries." Journal of Academic Librarianship 35.2 (2009): 143-51. Objective – To investigate the use of telephone interviews in academic libraries and identify best practices when conducting telephone interviews. Design – Survey and open-ended questions. Setting – Academic libraries in the United States. Subjects – Academic institutional members of the Association of Research Libraries. Methods – A fifteen-item survey (Appendix A, 150) concerning telephone interviewing practice was sent to 112 institutional members of the Association of Research Libraries (ARL). The survey contained multiple choice-type questions as well as open-ended questions. Main Results – The response rate was 66% (74 of 112 research libraries; 56 public institutions and 17 private). Of the respondents, 90% used telephone interviews to screen applicants for professional positions (ranging from occasionally to always) and only 10% never used telephone interviews. The main reason for holding telephone interviews was to “screen candidates in order to narrow the pool of applicants who will be invited for in-person interviews” (146). Other reasons given included minimizing expenses involved in interviewing out-of-town candidates (39% respondents), shortening the length of time to complete the search process (27%) and meeting library or campus hiring requirements (3%). On average, the majority of libraries (51%) hired between 2-4 professional positions each year. For each open professional position, the number of candidates telephone-interviewed varied from less than 3 to 9 depending on library and position. Interviews typically lasted between 16 and 45 minutes (77% respondents) with all the search committee members (staff involved in the recruitment process) being present (75%) and taking turns to ask questions to the candidates (90%). Questions were most often the same for all candidates applying for a particular position (91%) and candidates were nearly always allowed in return to ask questions of the committee (96%). In answer to the open-ended question, “In your opinion, what best creates a collegial and effective environment for conducting telephone interviews?”, the dominating responses included: all search committee members being present and participating actively, using a script and taking notes, introducing all interview participants, and giving candidates adequate notification and documentation. The majority of respondents “would not change anything about their institution’s current (telephone interview) practice” (147). Some thought that “training and/or a need for consistency in procedure for all interviews conducted” (147) would be relevant changes in practice. The results of the survey were compared to the findings in the library, personnel management and human resources literature. Conclusion – From the survey and responses to open-ended questions, a number of best practices when conducting telephone interviews emerged (148–150): 1. Properly train the search committee (e.g., in knowing about the position, organization and protocols for conducting interviews properly) 2. Involve the search committee throughout the recruitment process 3. Help the interviewee be prepared (e.g., by sending institutional information packages) 4. Maintain and use suitable technology (e.g., by choosing suitable conferencing facilities with the interviewee situation in mind) 5. Put the candidate at ease (e.g., by explaining who will be present, how long the interview will last and how many questions there will be) 6. Provide introductions (e.g., both in the beginning of the interview and even before individual questions) 7. Listen and take notes during the interview 8. Discuss the interviews immediately afterwards Engel and Robbins suggest that further research could include looking into job candidate and search committee experiences of the telephone interviewing procedure.